A monographic research on the Assyrian culinary culture in Turkey - Cagla Ozer (Journal of Ethnic Foods, 2019)
Abstract Assyrians are the oldest civilization of Mesopotamia and have a history of 5500–6000 years. They are known as the first civilization in history, founded in Antakya by Mor Petrus in 37–43 AD and briefly announcing Christianity to the whole Middle East. Today, it is estimated that there are 12 and a half million Assyrians in the world and 45,000 Assyrians in Turkey. Most of them live in different regions of Eastern Anatolia, mostly in Istanbul. The Ottoman Empire served as home to countless cultures and religions with its 500-year history, and this cultural wealth made a positive impact on the culinary culture, creating a unique kitchen. Various sources argue that the cultures of Assyrians, especially in the regions where Assyrians lived, constituted Assyrian culinary cultures with a dense population. In this study, the history of the Assyrian, the regions they lived extensively in the world and Turkey, and the beliefs and practices in birth, marriage, death, feast, and holy days have been examined in terms of gastronomic culture.